Values embedded in the Berasan tradition of Rejang ethnic wedding customs of Bengkulu - Serasi, Reko; Sarwono, Sarwit; Yulistio, Didi; Murwantono, Didik (EduLite: Journal of English Education, Literature and Culture, 2025)
This study seeks to thoroughly investigate the Berasan tradition within the Rejang ethnic group in Lebong Regency, Bengkulu Province, Indonesia. This study elucidates the ideals inherent in the Berasan heritage within the Rejang ethnic wedding customs of Bengkulu. This research employed qualitative approach with a descriptive methodology.The research instruments used in this study were observation sheets, in-depth interviews, as well as documentation.This study focused on the Rejang ethnic minority in Lebong Regency, Bengkulu Province, Indonesia. The informants utilized in this study comprised (1) the Customary Chief, (2) the Syara' Chief or Village Imam, (3) the Kutai Chief or Spokesperson for the prospective bride and groom, and (4) the Local Community Store. This study employed a triangulation data gathering technique utilizing research tools such as field observation, in-depth interviews, and documentary material. The data analysis method employed was inductive data analysis. The findings indicate that the rice tradition encompasses social and religious values, including (1) Mutual Cooperation, (2) Family, (3) Shared Responsibility, (4) Honesty and Openness, (5) Ethics and Politeness, (6) Respect for Ancestors, and (7) Good Intentions and Sincerity. This study concluded that the Berasan tradition constitutes a cultural heritage enriched with functional, symbolic, and pedagogical elements that are vital to conserve. The values embedded within it were found to serve as a meaningful reference for shaping social ethics in contemporary society.